The Post-Anthropological Indian: Canada’s New Images of Aboriginality in the Age of Repossession - Scheffel, David Z. (Anthropologica, 2022)
The article examines the new public imagery of Canadian Aboriginal peoples formulated in the 1980s and 1990s. Concentrating on the public education system, the author identifies the implementation of multicultural policies in the late 1970s and early 1980s as the starting point for auricular revisions which led to the emergence of a new set of representations of Indianness. The author argues that the new imagery is ideologically motivated and distorted, conveying the impression of Aboriginal perfection. A detailed analysis of works produced by the Shuswap Nation of British Columbia demonstrates how ethnographic texts—in this case those of James Teit—are used in the reconstruction of the Aboriginal past. The article ends with an overview of the anthropological literature on invented traditions and their use by indigenous emancipatory movements in several parts of the world.